THE VALUE OF JUSTICE AMONG STUDENTS IN THE JESUIT SCHOOLS: EXPERIENCE, REFLECTION AND ACTION - SJ, Virgilijus Saulius Saulius (Acta Paedagogica Vilnensia, 2008)
The article discusses the experience, understanding and practical implementation of justice among Jesuit secondary school students in Lithuania. A model of the notion of justice in Jesuit schools is proposed on the basis of the analysis of literature and of Jesuit normative documents. The model is a part of the community aspect of the three basic values of Jesuit schools. Justice is examined through the elements of the Ignatian pedagogical paradigms: experience, reflection and action. It has beeen determined that, in the area of justice, reflection is dominant, follwed by experience and action. It can be said that the values of justice do not unequivocally include all the dynamic of the Ignatian paradigm. The article demonstrates that truth as the foundation of human existence is understood very well by the students, but the application of truth is mediocre. The reason is that the experience of Jesuit secondary school students is not ample: personal truth is important to them, the I-thou relationship, but without the category we. The principle of justice in daily life is most often applied passively – students do not participate in an unjust act, but take no steps to stop unacceptable behavior. The conclusion is that the most painful experience of injustice at school as experienced by students is betrayal by friends and unjust evaluation by teachers. The students indicate lies and betrayal as the greatest violation of justice.